An Elementary Teacher’s Feelings of Self-Efficacy, Needs, and Pedagogical Strategies When Learning to Use the Interactive Whiteboard to Teach Science - Hart, Francine (Université d'Ottawa / University of Ottawa, 2014)
Studies have shown elementary teachers may not be well prepared to use technology in their classrooms. This study examines one elementary teacher’s feelings of technology self-efficacy (TSE), needs and pedagogical strategies when using the interactive whiteboard (IWB) to teach elementary science. It employed a single case study design, where the researcher and participant worked together during supportive professional development (PD) sessions. Data sources are twelve PD sessions, the Computer Technology Integration Survey (adapted for IWB use in the classroom), and two interviews, three in-class observations of IWB science lessons, and three lesson debriefs. Descriptive and thematic analysis show the participant’s TSE was positively influenced by the PD. Five factors were determined to influence TSE: the participant’s level of interest, attitude, experience with technology, student assistance, and familiarity with the setting. Teacher, contextual and IWB- level needs were explained. Pedagogical strategies for technology use based on interactive IWB features are also discussed. Findings could contribute to current trends in teacher PD, continuing education, and preservice teaching programs related to science teaching. / Plusieurs enseignants ne sont pas bien préparés pour utiliser la technologie en classe. En particulier, le tableau blanc interactif (TBI) n’est pas utilisé de façon optimale par les enseignants lorsqu’ils enseignent les sciences et la technologie à l’élémentaire. Cette thèse présente l’étude de cas unique d’une enseignante de l’élémentaire ayant cheminé dans un processus de développement professionnel (DP) pour l’aider à intégrer le TBI en sciences et technologie. Douze sessions de DP, un questionnaire sur l’efficacité avec le TBI (CTIS adapté), deux entrevues, trois sessions d’observation en classe et trois discussions sur les leçons constituent les sources de données. La participante est devenue plus confiante pour utiliser le TBI suite au DP. Elle a rehaussé son sentiment d’autoefficacité et accru son intérêt et sa connaissance du TBI. Elle a acquis des compétences techniques et une connaissance des contenus d’enseignement adaptés au TBI, bien que plusieurs besoins perdurent. Certaines stratégies pédagogiques avec le TBI expérimentées en classe par l’enseignante sont discutées. Cette thèse peut contribuer à fournir des pistes pour aider les enseignants au primaire à mieux intégrer le TBI en sciences et technologie, que ce soit lors de leur formation initiale à l’enseignement ou en cours d’emploi.
Keywords: Interactive Whiteboard (IWB); Science Education; Technology Self-Efficacy (TSE); Technological Needs; Pedagogical Strategies Using Technology; IWB Tools; Technology Integration; Thematic Analysis; Professional Development (PD); Elementary Science Teaching; Tableau blanc interactif (TBI); sciences et technologie; sentiment d’autoefficacité avec la technologie; besoins technologiques des enseignants; stratégies pédagogique avec le TBI; outils du TBI; l’intégration des technologies en salle de classe; analyse thématique; développement professionnel (DP); l’enseignement des sciences à l’élémentaire